Association Between Protein Intake and Mortality in Hypertensive Patients Without Chronic Kidney Disease in the OLD-HTA Cohort. Issue 6 (June 2016) - Courand, Pierre-Yves; Lesiuk, Chloé; Milon, Hugues; Defforges, Alice; Fouque, Denis; Harbaoui, Brahim; Lantelme, Pierre
Abstract : Protein intake may have some benefits on reducing blood pressure and cardiovascular events, but their effects are still debated. The objective of this study was to test the prognostic value of protein intake assessed by 24-hour urinary urea in a cohort of hypertensive patients with preserved renal function. A total of 1128 hypertensive patients were followed according to tertile of protein intake adjusted for ideal body weight: <0.70, 0.70 to 0.93, and >0.93 g/kg. Baseline characteristics (mean±standard deviation) were age 45.1±13.2 years, systolic/diastolic blood pressure 185±32/107±20 mm Hg, and estimated glomerular filtration rate 82±32 mL/min. After 10 years of follow-up, 289 deaths occurred, 202 of which were of cardiovascular cause. After adjustment for major cardiovascular risk factors, patients in the second and third tertiles of protein intake had a decreased risk of all-cause death (hazard ratio [95% confidence interval], 0.71 [0.56–0.91]) and cardiovascular death (0.72 [0.54–0.96]), but not of stroke death (0.72 [0.41–1.28]) in comparison to patients in the low protein intake tertile. Normal–high protein intake was associated with a better outcome in a subset of the population: younger patients, low salt intake, without aortic atherosclerosis, or previous cardiovascular events ( P interaction <0.10 for all). Hypertensive patients having a protein intake >0.7 g/kg ideal body weight, particularly those at low risk, had lower all-cause and cardiovascular mortality rates. Physicians may encourage hyper tensive patients to have normal or high protein diet in addition to low salt consumption, moderate alcohol consumption, and regular physical activity. Abstract : Supplemental Digital Content is available in the text.